2021
DOI: 10.3389/fnagi.2021.751369
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality Mediates the Association Between Cerebral Small Vessel Disease Burden and Frailty: A Community-Based Study

Abstract: Background: Physical frailty is a common problem among older adults which usually leads to adverse health outcomes. The imaging markers of cerebral small vessel disease (CSVD) are associated with frailty, but the underlying mechanisms remain unclear. The present study aimed to investigate the mediating role of sleep quality in the relationship between CSVD burden and frailty.Methods: We performed a cross-sectional study and enrolled community residents. Frailty and sleep quality were measured using the Fried f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The mean value of sleep quality was 6.1 ( SD 3.4) and more than half of the participants had poor sleep quality (values >5), similar to previous studies (Alqahtani, 2021; Zhao et al, 2021). Our results showed that subjective sleep quality, sleep latency (difficulty in falling asleep) and sleep disturbance had the highest scores for sleep problems in older people, similar to those of earlier studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean value of sleep quality was 6.1 ( SD 3.4) and more than half of the participants had poor sleep quality (values >5), similar to previous studies (Alqahtani, 2021; Zhao et al, 2021). Our results showed that subjective sleep quality, sleep latency (difficulty in falling asleep) and sleep disturbance had the highest scores for sleep problems in older people, similar to those of earlier studies.…”
Section: Discussionsupporting
confidence: 88%
“…The mean value of sleep quality was 6.1 (SD 3.4) and more than half of the participants had poor sleep quality (values >5), similar to previous studies (Alqahtani, 2021;Zhao et al, 2021). was significantly associated with the overall health after 1 year, supported by previous studies (Matsui et al, 2021;Sella et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Poor sleep quality is considered to be one of the non-traditional risk factors for cardiovascular and cerebrovascular diseases ( 6 , 7 ), and it is not only associated with cognitive decline ( 8 ) but also with development or exacerbation of other psychiatric symptoms ( 9 , 10 ). Prosperous sleep quality plays a vital role in consolidating memory, regulating immunity, and balancing homeostasis ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, sleep quality was assessed using The PSQI (38), which is used to evaluate better the sleep quality status of the study participants in the last month, and it is the most widely used subjective sleep assessment scale (39). The Chinese version of the scale currently in use has been shown to have good reliability and validity (40) and has been used in several studies (39,41), with a Cronbach's alpha of 0.736 in this study. The scale consists of 18 self-assessment items divided into seven dimensions, namely subjective sleep quality, sleep duration, time to fall asleep, sleep disorders, sleep e ciency, use of hypnotic medication, and daytime dysfunction, with scores ranging from 0 to 3 for each dimension, and a total score ranging from 0 to 21, with higher scores being associated with poorer sleep quality.…”
Section: Sleep Quality Assessmentmentioning
confidence: 99%